Psicopatología de los pacientes hospitalizados en el Hospital Regional Lambayeque, enero 2015 - Díaz-Nolazco, Marcel Alonso (2019)
Introduction: In the inpatients he expects to find him important levels of psychiatric symptoms. Scarce studies exist that psicopatologycal in inpatients for medical causes, in spite of the importance of these on the diagnosis, treatment, evolution and costs of attention evaluate the prevalence of alterations. Objetive: To objective of this study is describing the existence of psicopatologycal of the inpatients in the Hospital Regional Lambayeque in January 2015. Material and methods: Study observational, Descriptive, Prospect, Transversal – Analytic. Population: 351 inpatients during January 2015, distributed in the services of internal Medicine, General Surgery, gineco obstetrics and surgery of specialties. Show: 183 patients, with a loss of 3 all-comers. Previous informed consent applied over itself the collecting chip of data and General Health Questionaire - 12, during January of 2015. The shrunk data analyzed him with the program SPSS version 19,0. Results: The presence of psychopathology in the studied population belonged to 45 % with some indisposition psicopatologycal. Conclusions: If there exists psicopatologycal in the inpatients in the Hospital Regional Lambayeque, during January 2015.